Gendered Implications of Customary Laws on the Women of Zeliangrong Naga - JANGMEI, RIAMEI (Journal of Advanced Research in Humanities and Social Sciences; Vol 9 No 4 (2022): Journal of Advanced Research in Humanities and Social Sciences, 2022)
Customary laws are established as social practises that are used as a means of social control and sanction in many tribal societies of North East India, including Zeliangrongs. The paper will examine the teeming precedence in which women are perpetually entangled in various problematic situations when bargaining their spaces pertaining to marriage and inheritance rights, with a focus on the patriarchal and patrilineal Zeliangrong tribe. It also seeks to explore how the patriarchal Zeliangrong society’s social structures cloak women’s development and bolster their invisibility and mute presence. Despite high literacy, power, prestige, privileges remain concentrated in the hands of a few (especially men). The paper also aims to uncover how customary laws have attributed to women’s oppression by denying them social, political, and economic security. How to cite this article: Jangmei R. Gendered Implications of Customary Laws on the Women of Zeliangrong Naga. J Adv Res Humani Social Sci 2022; 9(4): 19-25.